APPLICATION OF ESP TECHNOLOGIES IN TEACHING ENGLISH TO AGMK WORKERS USING DIGITAL TOOLS - Paizbekova Aziza Djaksinovna (Uzbekistan Open Conference, 2026)
The article examines the application of ESP (English for Specific Purposes) technologies in teaching English to workers in the mining and metallurgical industry. Special attention is given to the use of digital tools, including online platforms and artificial intelligence technologies, to improve learning effectiveness. The study presents a course program developed for AGMK workers at the elementary level. The results show that the use of ESP and digital tools enhances motivation and improves the acquisition of professional vocabulary.
Keywords: ESP; English language; digital technologies; artificial intelligence; professional training; industry